PENDAMPINGAN DIVERSIFIKASI PRODUK OLAHAN SUSU DAN PENGUATAN MARKETING PADA KELOMPOK TANI NEDYO RAHAYU DI DESA WUNGU KABUPATEN MADIUN - Nia Agustina; Paramita Wisnuwardhani (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
Fresh milk is perishable, so without further processing, its selling value is low and it is vulnerable to market price fluctuations. This is the situation faced by the Nedyo Rahayu Farmers Group in Wungu Village, Madiun Regency, which has only marketed raw milk. This community service activity aims to assist the farmer group in developing diversified high-value dairy products while formulating effective marketing strategies to expand market reach. The activity was attended by 25 participants who are members of the Nedyo Rahayu Farmers Group. The method used was a qualitative descriptive approach through field observations, in-depth interviews with group administrators, activity documentation, and training and mentoring on milk processing. The activity results showed the birth of four innovative products: yogurt, mozzarella cheese, milk patties, and various flavored pasteurized milk, which were strengthened by strengthening branding, improving packaging, and implementing digital marketing. Evaluations showed a 32% increase in participants' knowledge regarding product diversification, food safety, and marketing strategies, as well as a 38% increase in skills in the production, packaging, and marketing of dairy products. This activity concluded that the combination of product innovation and marketing strategies was able to increase the economic added value of fresh milk and encourage the growth of independent micro-business units based on milk processing in Wungu Village, Madiun Regency.